Industrial Digital Transformation Accelerate Digital Transformation with Business Optimization, AI, and Industry 4. 0. - Nath, Shyam Varan (Packt Publishing, Limited, 2020)
Delve into industrial digital transformation and learn how to implement modern business strategies powered by digital technologies as well as organization and cultural optimizationKey FeaturesIdentify potential industry disruptors from various business domains and emerging technologiesLeverage existing resources to identify new avenues for generating digital revenueBoost digital transformation with cloud computing, big data, artificial intelligence (AI), and the Internet of Things (IoT)Book DescriptionDigital transformation requires the ability to identify opportunities across industries and apply the right technologies and tools to achieve results. This book is divided into two parts with the first covering what digital transformation is and why it is important. The second part focuses on how digital transformation works.After an introduction to digital transformation, you will explore the transformation journey in logical steps and understand how to build business cases and create productivity benefit statements. Next, you'll delve into advanced topics relating to overcoming various challenges. Later, the book will take you through case studies in both private and public sector organizations. You'll explore private sector organizations such as industrial and hi-tech manufacturing in detail and get to grips with public sector organizations by learning how transformation can be achieved on a global scale and how the resident experience can be improved. In addition to this, you will understand the role of artificial intelligence, machine learning and deep learning in digital transformation. Finally, you'll discover how to create a playbook that can ensure success in digital transformation.By the end of this book, you'll be well-versed with industrial digital transformation and be able to apply your skills in the real world.What you will learnGet up to speed with digital transformation and its important aspectsExplore the skills that are needed to execute the transformationFocus on the concepts of Digital Thread and Digital TwinUnderstand how to leverage the ecosystem for successful transformationGet to grips with various case studies spanning industries in both private and public sectorsDiscover how to execute transformation at a global scaleFind out how AI delivers value in the transformation journeyWho this book is forThis book is for IT leaders, digital strategy leaders, line-of-business leaders, solution architects, and IT business partners looking for digital transformation opportunities within their organizations. Professionals from service and management consulting firms will also find this book useful. Basic knowledge of enterprise IT and some intermediate knowledge of identifying digital revenue streams or internal transformation opportunities are required to get started with this book.